Letter : Spanish seamen: emigration - Brooke, Eileen E.
025a-0044-001 46 Kingsway London W.C.2 Tel Holborn 6585 May 6th., 1940. Your ref: International. HVT/AC/DT/901. Dear Mr. Tewson, SPANISH SEAMEN - EMIGRATION. Thank you for your letter of the 3rd. May, giving details of Spanish seamen and their dependants who wish to emigrate. Sr. Azcárate is leaving again for Paris this week, so I will hand him your letter and the attached list, in order that he can take up the question with the S.E.R.E. direct. I will get in touch with you again on this matter immediately after Sr. Azcárate's return to this country. Yours sincerely, E.E. Brooke H.V. Tewson, Esq., Trades Union Congress, Transport House, S.W.1. 292/946/25a/44